DORMANT ACCOUNT SETTLEMENT STRATEGY IN HANDLING COMPLAINTS AT PT BANK SUMUT SYARIAH BRANCH OFFICE HM YAMIN MEDAN - Yuli Andini; Ahmad Syakir; Muhammad Lathief Ilhamy Nasution (Postgraduate Bosowa University Publishing, 2026)
Dormant accounts represent an important challenge in Islamic banking because they indicate declining customer transaction activity, reduced engagement, and potential decreases in customer loyalty. This study aims to analyze the dormant account settlement strategy implemented by PT Bank Sumut Syariah KCP HM Yamin Medan and examine its relationship with service quality and customer complaint handling. The study employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation, and analyzed using the Unified Theory of Acceptance and Use of Technology (UTAUT) and SWOT analysis. The findings reveal that from April 2025 to February 2026, there were 159 dormant accounts, primarily caused by low transaction intensity, changing customer preferences, limited access to banking facilities, and increasing competition among banking institutions. The bank has implemented a structured settlement strategy through automatic account categorization, customer verification, and account reactivation procedures based on prudential banking principles. However, the existing approach remains largely administrative and has not fully addressed the underlying behavioral and service-related factors contributing to account inactivity. The study further indicates that dormant accounts are closely associated with customer satisfaction, service quality, and relationship management. Therefore, Islamic banks need to adopt a more proactive strategy by strengthening customer communication, optimizing digital banking services, and enhancing customer engagement programs. These efforts are expected to reduce the growth of dormant accounts, improve customer loyalty, and support the sustainability of third-party funds in Islamic banking institutions.